INTEGRATION OF IJARAH AND MUKHABARAH: A STUDY ON AGRICULTURAL LAND COOPERATION IN NAGARI PAKAN RABAA, KOTO PARIK GADANG DIATEH DISTRICT, SOUTH SOLOK REGENCY - Linda, Nova; Yustiloviani, Yustiloviani; Zainuddin, Zainuddin; Husni, Alfi (UIN Mahmud Yunus Batusangkar, 2024)
This thesis examines the integration of ijarah and mukhabarah practices in agricultural land cooperation in Nagari Pakan Rabaa, Koto Parik Gadang Diateh District, South Solok Regency. The study aims to analyze and explain the implementation of mukhabarah and ijarah practices and their integration in agricultural land cooperation in the community. A qualitative field research approach was adopted, with data collected through interviews with landowners and cultivators. Data analysis followed the Miles and Huberman framework, involving data reduction and presentation, with validity ensured through source triangulation.The primary data sources included six informants: three landowners and three cultivators in Nagari Pakan Rabaa. Secondary data sources comprised information from a local religious leader (buya), as well as references from the Qur’an, Hadith, scholarly opinions, journals, and articles.The findings reveal that mukhabarah cooperation is practiced by landowners transferring land to cultivators, with seeds, fertilizers, and land preparation costs borne by the cultivators. The harvest is then divided, with 40% allocated to the landowner and 60% to the cultivator. Meanwhile, ijarah practices involve cultivators directly renting land from the landowners. In this system, the cultivators bear all farming costs, and rental payments are made annually at the end of the lease, either in cash (Rp. 2,000,000) or as rice (90 bushels).The integration of mukhabarah and ijarah occurs when landowners offer land to cultivators, who then manage all farming expenses. An agreement is established that the harvest will be shared (40% for the landowner, 60% for the cultivator), and cultivators must also pay an annual land rent at the end of the lease. This integrated practice reflects the community’s adaptive approach to balancing traditional Islamic principles with local agricultural needs.